2012
DOI: 10.1074/jbc.m112.359976
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chloroplastic Fructose 1,6-Bisphosphate Aldolases as Lysine-methylated Proteins in Plants

Abstract: Background:The protein-lysine methyltransferase LSMT from pea methylates the large subunit of Rubisco. Results: In Arabidopsis, Rubisco is not methylated, and the physiological substrates of the LSMT-like enzyme are chloroplastic aldolases. Conclusion: LSMT homologs from plants display different substrate specificities, with targets involved in carbon metabolism. Significance: The study identifies chloroplastic aldolases as new lysine-methylated proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
80
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 36 publications
6
80
0
Order By: Relevance
“…Acetylation and methylation of chloroplast proteins have been identified recently (Houtz et al, 1992;Finkemeier et al, 2011;Wu et al, 2011;Mininno et al, 2012;Alban et al, 2014). Therefore, the acetylation and methylation states of the four membrane-bound AtFNR forms were analyzed.…”
Section: Atfnr1 and Atfnr2 Are Lys Acetylatedmentioning
confidence: 99%
“…Acetylation and methylation of chloroplast proteins have been identified recently (Houtz et al, 1992;Finkemeier et al, 2011;Wu et al, 2011;Mininno et al, 2012;Alban et al, 2014). Therefore, the acetylation and methylation states of the four membrane-bound AtFNR forms were analyzed.…”
Section: Atfnr1 and Atfnr2 Are Lys Acetylatedmentioning
confidence: 99%
“…Moreover, three isoforms of chloroplast FRU-1,6-BISPHOSPHATE ALDOLASE have been found to contain trimethylated Lys residues in close proximity to their C termini. No differences, however, could be detected in the catalytic activity, stability, or oligomerization between the trimethylated and unmodified enzymes (Mininno et al, 2012).…”
Section: Lys and Arg Methylationmentioning
confidence: 84%
“…A recent study has identified 23 chloroplast methylproteins (Alban et al, 2014), including the previously described ALDOLASE isoforms (Mininno et al, 2012) and PLASTID RIBOSOMAL PROTEIN L11 (Yamaguchi and Subramanian, 2000). Four out of these 23 proteins contained one or more methylated Arg residues, while 17 proteins had Lys methylation.…”
Section: Lys and Arg Methylationmentioning
confidence: 97%
See 2 more Smart Citations